If you build it, he will come: Anticipative power transmission planning - Pozo, David; Contreras, Javier; Sauma, Enzo (Energy economics, 2013)
Like in the film Field of Dreams, the sentence “if you build it, he will come” also applies in power systems. In this sense, if a transmission planner suggests building some lines in anticipation of generation capacity investments, then it can induce generation companies to invest in a more socially efficient manner. In this paper, we solve for the optimal way of doing this anticipative power transmission planning. Inspired in the proactive transmission planning model proposed by Sauma and Oren (2006) we formulate a mixed integer linear programming optimization model that integrates transmission planning, generation investment, and market operation decisions and propose a methodology to solve for the optimal transmission expansion. Contrary to the proactive methodology proposed by Sauma and Oren (2006), our model solves the optimal transmission expansion problem anticipating both generation investment and market clearing. We use the marginalist theory with production cost functions inversely related to the installed capacity in a perfectly competitive electricity market and we find all possible generation expansion pure Nash equilibria. We illustrate our results using 3-node and 4-node examples. ► We formulate a mixed integer linear programming model for transmission planning. ► We integrate transmission and generation investments, and market operation decisions. ► Our model solves for the optimal transmission expansion using the marginalist theory. ► We illustrate our results using 3-node and 4-node examples.